(untitled) (Международный научный журнал «Инженер», 2026)
The paper examines copper and copper-zinc coatings (such as "brass") obtained by the method of "cold" gas-dynamic spraying. The X-ray diffraction phase analysis method revealed that zinc is the main element that "captures" corundum particles, but it cannot "retain" corundum particles under the influence of a conjugated surface, having separated from the coating surface, they have a significant effect on friction processes in the tribological pair. Two mechanisms are proposed that describe the effect on the nature of the change in the microgeometry of the surface of the counterbody and its wear. Tests of copper-zinc coating of brass type in the medium of industrial oil paired with steel ShKh15 showed low wear intensity up to the effect of non-wear without deterioration of the surface quality of the friction pair.